Model Pendidikan Anti Korupsi di Sekolah Dasar dalam Mewujudkan Generasi Yang Bersih dan Berintegritas Sejak Dini - Nuzus Sakinah; Nurhasanah Bakhtiar (el-Ibtidaiy:Journal of Primary Education, 2019)
Indonesia is the most corrupt country among 12 Asian countries. so that prevention aspects in the form of Anti-Corruption Education (PAK) need to be implemented. The purpose of this study is to explore the Anti-Corruption Education model in lementaryschools in realizing a generation that is clean and has integrity. This research is a library research or library research which aims to study text, books, and publication texts regarding content analysis models, namely the application of Anti-Corruption Education. As well as the results expected in this study the first presentation about the meaning of corruption, features of corruption, forms of corruption, causes of corruption and the impact of corruption. Second, holding a film screening about corruption and the latter using an anti-corruption education model to be implemented for early childhood